MARX, Karl. Nova Gazeta Renana. [Apresentação e tradução: Lívia Cotrim]. São Paulo: Educ, 2010 (612 p.) - REA Editor (Revista Espaço Acadêmico, 2012)
MARX, Karl. Nova Gazeta Renana. [Apresentação e tradução: Lívia Cotrim]. São Paulo: Educ, 2010 (612 p.)